2009
DOI: 10.1016/j.jcrs.2009.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Using Rasch analysis to revisit the validity of the Cataract TyPE Spec instrument for measuring cataract surgery outcomes

Abstract: With minor modifications, the Cataract TyPE Spec questionnaire and its glare and near-vision subscales were good measures of visual functioning in the cataract patient. Additional items to suit the more able, including patients having second-eye surgery, could improve the measurement properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…6,[12][13][14] The VSQ also shares the same deficiency and the claim that it is specifically suited to measuring outcomes in second-eye surgery patients cannot be confirmed. Indeed, 2 items specifically designed for second-eye patients (difficulty pouring liquids and judging distances) were 2 of the 3 easiest items, as shown by their position at the top of the person-item map ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[12][13][14] The VSQ also shares the same deficiency and the claim that it is specifically suited to measuring outcomes in second-eye surgery patients cannot be confirmed. Indeed, 2 items specifically designed for second-eye patients (difficulty pouring liquids and judging distances) were 2 of the 3 easiest items, as shown by their position at the top of the person-item map ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous studies [12][13][14][15][16][17] found that these questionnaires are not sensitive to patients having second-eye surgery because of a ceiling effect (ie, high percentage of responses in the most able end category of the response categories). Ceiling effects occur when patients are able to perform all activities listed in a questionnaire; that is, they record a score of no disability (full functioning).…”
mentioning
confidence: 97%
“…In our study, patients with other ocular diseases were not included; indeed, the percentage of cataract surgery patients with ocular comorbidities varies from 25.0% to 47.9%. 10,11 Because ocular comorbidities can affect the results of the cataract surgery, it would be interesting to assess the satisfaction in this population.…”
Section: Discussionmentioning
confidence: 99%
“…3 Other instruments to assess cataract surgery outcomes have been validated using Rasch analysis. [10][11][12] For example, the Impact of Visual Impairment questionnaire was validated in a cataract population. 10 This questionnaire measures cataract surgery outcome results across 3 subscales of participation in activities of daily living (reading and accessing information, mobility and independence, and emotional well-being).…”
mentioning
confidence: 99%
“…Content [7,12], construct [3] and predictive [13] validity is crucial in getting the sufficient result of the study. Survey questionnaire in this research used two types of scale.…”
Section: Motivationmentioning
confidence: 99%